READERS’ RESPONSE TO MAMAN SUHERMAN’S RE - MURNI AZURA; AMRIN SARAGIH; SRI MINDA MURNI (LINGUISTICA, 2021)
The topic of the research is Readers' Reactions to Maman Suherman's Re: The study's goals were to look at the readers' reactions to the plot components in Maman Suherman's Re: and the reasons for their reactions to Maman Suherman's Re: The descriptive qualitative method was used in this study's investigation. The readers' responses to the novel's questionnaire served as the study's data. The information was gathered from readers who had completed the novel in its entirety. The outcome revealed how readers reacted to Maman Suherman's Re: Beach, and Marshall's theory was used to examine the data. The reader liked the story elements in Maman Suherman's Re: the reader liked the story elements in Maman Suherman's Re: the reader liked the story elements in Maman Suherman's Re: the reader liked the story elements in Maman Suherman's Re: the reader liked the story elements in Maman Suherman's Re: the reader liked the story elements in Maman Suherman's Re